2011
DOI: 10.1016/j.ijfatigue.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion fatigue behaviour of aluminium alloy 6061-T651 welded using fully automatic gas metal arc welding and ER5183 filler alloy

Abstract: The fatigue life of aluminium 6061-T651 at various applied stress amplitudes in the unwelded and welded condition was found to be significantly reduced on immersion in a 3.5% NaCl simulated sea water solution, compared to that measured in ambient air. The ratio of fatigue life in NaCl test solution to that in air increased as the stress amplitude decreased. The observed reduction in the fatigue life in the NaCl test solution was most likely due to the presence of pits which nucleated on second phase particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…The aluminum alloys from the 6000 family series has been the most considered for substantial use in industry. This arises from its appropriate weldability and high corrosion behavior (Fahimpour et al [8]; Mutombo and Toit [9]). In particular in this family, such as in 6061, the most commonly used material which is the main alloying element is silicon (Si).…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum alloys from the 6000 family series has been the most considered for substantial use in industry. This arises from its appropriate weldability and high corrosion behavior (Fahimpour et al [8]; Mutombo and Toit [9]). In particular in this family, such as in 6061, the most commonly used material which is the main alloying element is silicon (Si).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the result of corrosion may induce not only crack tip closure but also embrittlement due to the entry of hydrogen into the interstices of the alloy. The factor that will cause each of these two phenomena to predominate in fatigue crack propagation is the loading type, such as stress level, load ratio, constant or random amplitude, and frequency of testing [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of these localized corrosion defects such as pit geometry [18,19], micro-topographic strain concentration and local stress distribution around pit [20] are essential in determining the pit-to-crack transition such as fatigue life tests performed on pre-corroded samples. Mutombo and du Toit have characterized the fatigue-corrosion endurance behavior of a welded 6061-T651 aluminum alloy in a 3.5% (by weight) NaCl solution at various applied stress amplitudes [21]. The reduction in the fatigue life in the corrosive solution compared to the fatigue life in air was also most strongly related to the presence of pits, which nucleated on second-phase particles or precipitates and acted as preferential fatigue crack initiation sites.…”
Section: Introductionmentioning
confidence: 99%